Benefits of Motor Imagery for Human Space Flight: A Brief Review of Current Knowledge and Future Applications - Guillot, Aymeric; Debarnot, Ursula (Frontiers in Physiology, 2019)
Motor imagery (MI) is certainly one of the most remarkable capacities of the human mind, and there is now strong experimental evidence that MI contributes to substantially improve motor learning and performance. MI therapeutic benefits designed to promote motor recovery in case of motor impairments have also largely been reported in the literature. Despite promising theoretical and experimental studies, whether MI might be effective in unusual conditions, such as weightlessness during space flight, has received far less attention. In the present review, we consider how, why, where and when MI might be used by astronauts, and further question what should be ideally imagined. Practically, we postulate that MI might be performed before, during and after exposure to microgravity, respectively to prepare for the sudden lack of gravity after launch, reduce the adverse effects of weightlessness exposition, and facilitate re-adaptation when returning to Earth after long exposure to microgravity.